2018
DOI: 10.1101/267583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular rack and pinion actuates a cell-surface adhesin and enables bacterial gliding motility

Abstract: The mechanism for bacterial gliding is not understood. The gliding bacterium Flavobacterium johnsoniae is known to have an adhesin, SprB, that moves along the cell surface on a spiral track. When cells are sheared by passage of a suspension through thin tubing, they stop gliding but can be tethered by addition of an anti-SprB antibody. Tethered cells spin about 3 Hz. We labeled the Type 9 secretion system (T9SS) with a yellow-fluorescent-protein (YFP) fusion of GldL. When labeled cells were tethered, a yellow … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The third type of ion-driven motor is found in certain Bacteroidetes where it is used to power gliding motility across solid surfaces 6 using the proton motive force (PMF) across the inner membrane (IM) as the energy source 7 , 8 , 9 . The gliding motility motor generates a rotary motion at the cell surface 9 that results in a helical flow of surface adhesin proteins 7 , 10 , 11 , possibly by driving a mobile track to which the adhesins are attached 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The third type of ion-driven motor is found in certain Bacteroidetes where it is used to power gliding motility across solid surfaces 6 using the proton motive force (PMF) across the inner membrane (IM) as the energy source 7 , 8 , 9 . The gliding motility motor generates a rotary motion at the cell surface 9 that results in a helical flow of surface adhesin proteins 7 , 10 , 11 , possibly by driving a mobile track to which the adhesins are attached 12 .…”
Section: Introductionmentioning
confidence: 99%
“…T9SS containing Bacteroidetes are abundant in the human oral and gut microbiota. A large cell-surface protein SprB acts as a focal adhesin and it facilitates T9SS driven bacterial gliding motility 35 . Besides aiding in motility, SprB also binds to non-motile bacterial species.…”
Section: Resultsmentioning
confidence: 99%
“…Motile members of the phylum Bacteroidetes exhibit gliding motility with the help of the Type 9 Secretion System 32,33 . Bacteroidetes gliding motility is driven by a rotary motor 34 that couples with a cell-surface track 35 . C. gingivalis moves over an external surface with the help of a cell surface adhesin SprB 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Domains D1 to D4 of GldM shared the same straight topology, whereas in PorM there was ~ 45° bend between domain D2 and D3 [ 37 ]. Based on the observation of SprB circular motion in sheared cells [ 39 ] and the localisation of YFP-labelled GldL close to the centre of that rotation, Shrivastava et al [ 40 ] recently predicted GldLM to be the motor of the T9SS and showed that it was driven by the proton motif force (PMF). This was confirmed by Hennell-James et al [ 41 ] (non-peer-reviewed), by solving the native structure of the GldLM /PorLM complexes using cryo-EM.…”
Section: Structurementioning
confidence: 99%